A Comprehensive Study on Assessment of Prescription at Tertiary Care Hospital, Kathmandu, Nepal - Giri, Usha; Paudel, Sujan; Baniya, Deepti Piya; Adhikari, Pharsuram; Shrestha, Sabin; Bajracharya, Mijala (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Assessment of prescription can prevent medication errors and prevent adverse effects related with prescribing and patients related factors at health-care setting resulting the decline in morbidity, mortality and treatment burden for patients. Hence, this study was conducted to analyze prescription writing for its completeness occurred in a tertiary care hospital at Nepal.Method: A cross sectional, descriptive, prospective study was conducted at Manmohan Memorial Medical College and Teaching Hospital (MMTH), Kathmandu, Nepal during a time period from November 2023 to January 2024. A random sample of 394 prescriptions of patients were collected and reviewed from the outpatient department of the Hospital and filled in a pretested designed Performa containing prescriber information, patient information, diagnosis, superscription, inscription, subscription, signature. It is noted that whether this information mentioned properly or not by the prescriber at hospital setting.Results: The study found completeness of prescription regarding the name, age, sex and address of the patients. The data of prescribers regarding the prescriber’s name, qualification, Nepal Medical Council (NMC) registration number, signature and diagnosis were found to be 55.60%, 97.20%, 97.20%, 11.4% and 0.5% respectively. Dosage form, quantity, duration, dose, strength, frequency and route of administration were mentioned in 98%, 3.80%, 96.2%, 96.70%, 86.81%, 99% and 34% of the prescriptions respectively. Likewise, unauthorized abbreviation, illegible handwriting was found in 26.90%, 9.60% of the cases.Conclusion: Overall, regular prescription assessments are essential to detect errors and drive continuous improvement in prescribing practices.